Association Between Cardiac Surgery and Mortality Among Patients With Infective Endocarditis Complicated by Sepsis and Septic Shock. Issue 5 (May 2018) - Krajinovic, Vladimir; Ivancic, Stipe; Gezman, Petar; Barsic, Bruno
ABSTRACT: Background: Sepsis and septic shock are common presentations of infective endocarditis (IE), but little is known about clinical characteristics in this group of patients, use of surgical treatment, and their associations with outcome. We sought to determine the influence of cardiac surgery (CS) on the outcome of patients with IE in different stages of sepsis severity. Methods: Two hundred ninety four patients with definite IE native or prosthetic valve IE admitted between 2000 and 2011. Prospective evaluation using multivariable logistic regression to evaluate clinical characteristics and outcomes (in-hospital and 1-year mortality) in surgically and medically treated patients stratified by severity of sepsis and using new Sepsis-3 definitions. Results: The presence of sepsis or septic shock during IE showed a statistical relationship with increased in-hospital mortality (odds ratio [OR] 8.915, P  < 0.001 and OR 35.969, P  < 0.001, respectively) after adjusting for other risk factors of poor outcomes (neurological complications, congestive heart failure, and Staphylococcus aureus IE). Surgical treatment had a positive influence on in-hospital mortality in patients with sepsis or septic shock and IE (OR 5.157, P  < 0.001) as well as on 1-year survival (hazard ratio 3.092, P  < 0.001). Conclusions: The presence of sepsis or septic shock as defined in Sepsis-3 definitions is associated with unfavorable outcomes in patients with IE. Surgical treatment has a positive effect on outcomes (in-hospital mortality and 1-year survival) in patients with IE and sepsis or septic shock.